2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8857154
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Automatic Identification of Respiratory Disease from Acoustic Recordings

Abstract: This paper evaluates the use of breath sound recordings to automatically determine the respiratory health status of a subject. A number of features were investigated and Wilcoxon Rank Sum statistical test was used to determine the significance of the extracted features. The significant features were then passed to a feature selection algorithm based on mutual information, to determine the combination of features that provided minimal redundancy and maximum relevance. The algorithm was tested on a publicly acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…We also compared the performance of our system with reported works by Kok et al [12] and Chambers et al [6]. The average accuracies for both the systems along with the proposed system are provided in Table 10.…”
Section: Comparative Studymentioning
confidence: 97%
See 2 more Smart Citations
“…We also compared the performance of our system with reported works by Kok et al [12] and Chambers et al [6]. The average accuracies for both the systems along with the proposed system are provided in Table 10.…”
Section: Comparative Studymentioning
confidence: 97%
“…The average accuracies for both the systems along with the proposed system are provided in Table 10. Kok et al [12] 87.10 Chambers et al [6] 85.00 Proposed technique 99.22…”
Section: Comparative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the automated detection or analysis of respiratory sounds has some precedents [2], [3], [4], but has drawn increasing attention in recent years as robust machine hearing methods have been developed, leveraging on ever more capable deep learning techniques. Most existing respiratory sound analysis systems tend to rely upon frame-based feature representations such as Mel-Frequency Cepstral Coefficients (MFCC) [5], [6], borrowed from the Automatic Speech Recognition (ASR) and Speaker Recognition (SR) fields. However, Grønnesby et al [7] found that MFCCs did not represent crackles well.…”
Section: Introductionmentioning
confidence: 99%
“…Next, they applied a Maximal Information Coefficient (MIC) [11] to score each feature, selected only the most influencing, before feeding into a classifier to improve performance and reduce complexity. Similarly, Kok et al [6] applied the Wilcoxon Sum of Rank test to indicate which features among MFCCs, Discrete Wavelet Transform (DWT) and a set of time domain features (namely power, mean, variance, skewness and kurtosis of audio signal) mainly affected final classification accuracy. Image processing techniques were then tried by Sengupta et al [12], who employed Local Binary Pattern (LBP) analysis on mel-frequency spectral coefficients (MFSCs) to capture texture information from the MFSC spectrogram, thus obtained an LBP spectrogram.…”
Section: Introductionmentioning
confidence: 99%